Acute pyelonephritis in pregnancy: a case series at Institute of Kidney Diseases and Research Centre - Mishra, Vineet V.; Rane, Priyanka H.; Choudhary, Sumesh D.; Shah , Kunur N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Acute pyelonephritis is one of the most common indications for antepartum hospitalization, estimated at approximately 9.7% of all indications for predelivery hospitalization, and when diagnosed, conventional treatment includes intravenous fluid and parenteral antibacterial administration, and careful monitoring of fluid balance. Here, we present four cases of acute pyelonephritis in pregnancy treated and patient successfully delivered with healthy babies.